Probabilistic vs. deterministic fiber tracking and the influence of different seed regions to delineate cerebellar‐thalamic fibers in deep brain stimulation. (2nd May 2017) - Schlaier, Juergen R.; Beer, Anton L.; Faltermeier, Rupert; Fellner, Claudia; Steib, Kathrin; Lange, Max; Greenlee, Mark W.; Brawanski, Alexander T.; Anthofer, Judith M.
Abstract: This study compared tractography approaches for identifying cerebellar‐thalamic fiber bundles relevant to planning target sites for deep brain stimulation (DBS). In particular, probabilistic and deterministic tracking of the dentate‐rubro‐thalamic tract (DRTT) and differences between the spatial courses of the DRTT and the cerebello‐thalamo‐cortical (CTC) tract were compared. Six patients with movement disorders were examined by magnetic resonance imaging (MRI), including two sets of diffusion‐weighted images (12 and 64 directions). Probabilistic and deterministic tractography was applied on each diffusion‐weighted dataset to delineate the DRTT. Results were compared with regard to their sensitivity in revealing the DRTT and additional fiber tracts and processing time. Two sets of regions‐of‐interests (ROIs) guided deterministic tractography of the DRTT or the CTC, respectively. Tract distances to an atlas‐based reference target were compared. Probabilistic fiber tracking with 64 orientations detected the DRTT in all twelve hemispheres. Deterministic tracking detected the DRTT in nine (12 directions) and in only two (64 directions) hemispheres. Probabilistic tracking was more sensitive in detecting additional fibers (e.g. ansa lenticularis and medial forebrain bundle) than deterministic tracking. Probabilistic tracking lasted substantially longer than deterministic. Deterministic tracking was more sensitive in detecting the CTC than the DRTT. CTC tracts were located adjacent but consistently more posterior to DRTT tracts. These results suggest that probabilistic tracking is more sensitive and robust in detecting the DRTT but harder to implement than deterministic approaches. Although sensitivity of deterministic tracking is higher for the CTC than the DRTT, targets for DBS based on these tracts likely differ. Abstract : Probabilistic tracking (green) based on 64 diffusion gradient orientations showed the dentate‐rubro‐thalamic tract (DRTT) along the same path as deterministic tracking with 12 gradient orientations (yellow). However, the probabilistic approach detected the DRTT in more brains than the deterministic approach. Superior to the ventral thalamus the deterministic solution merged with the pyramidal tract, whereas the probabilistic solution diverged into additional tracts such as the ansa lenticularis.